La discussion philosophique avec les enfants : Une dispositif communicationnel égalitaire comme pratique éducative de l’ouverture d’esprit. - Johanna Hawken (Éducation et Socialisation)
Children develop and experience numerous thinking skills in the course of a philosophical dialogue, which is the didactic medium for the practice of philosophy with children, since its birth. One of them plays a paramount role in the possibility of true dialogue, as it relies on the meeting of minds: open-mindedness. Furthermore, this concept is omnipresent in the literature about philosophy for children (Lipman, 2003 ; Tozzi, 2001) and thus, requires an exploration and a precis analysis, which is the aim of his article. More precisely, there are three objectives: define the nature and characteristics of open-mindedness, analyse its emergence in philosophical discussions and, moreover, studying its role in the practice of philosophy. Our research (lead in the French town of Romainville, East of Paris, with the University Paris 1 Panthéon-Sorbonne) has shown that certain indicators present in the children’s discourse manifest the occurrence of open-mindedness: reformulation of one another’s words, complementarity of statements, explication of each other’s ideas, establishment of nuances, disagreement on terms and critical thinking. These cognitive acts reveal an intellectual relation between children, so much so as open-mindedness can be defined as a two-dimensional attitude, both as a cognitive disposition enabling the understanding of someone else’s idea and an ethical disposition enabling the acceptance of alterity. Moreover, it signals an ethical posture: the capacity to take embrace the words of others, without necessarily agreeing, the ability to take into account an alternative view on the world. We arrive at the following research hypothesis: philosophical discussions constitute an opportunity for children to experience open-mindedness as a crucial thinking skill and ethical posture.